Simultaneous spectrophotometric method for determination of both ciprofloxacin and cephalexin by using H-point standard addition method - Kawther Ahmed Sadiq; Elham N. Mezaal; Maha A. Mohammed; Dheefaf F. hassan (مجلة بغداد للعلوم, 2024)
An easy, simple and accurate method for estimating ciprofloxacin in the presence of cephalexin or vice versa in a mixture of the two. It has been possible to successfully apply the proposed method H-point standard addition method (H-PSAM) in the estimation of ciprofloxacin in the presence of cephalexin interfering at wavelengths 240-272.3 nm and with different concentrations of ciprofloxacin 4-18 μg.ml-1. As well as the estimation of the cephalexin in the presence of ciprofloxacin interfering at wavelengths 262-285.7 nm and with different concentrations of cephalexin 6-18 μg.ml-1 in a mixture of them. The results showed the absence of any interferences by the additives that the drugs may contain on these compounds and within the detection limits of ciprofloxacin equal to 0.1732 μg.ml-1 and drug cephalexin equal to 0.4620 μg.ml-1. RSD% less than 2%. The method has been successfully applied for the determination of the two drugs in some pharmaceutical preparations. The proposed method is considered one of the low-cost methods and it does not need to introduce the properties in a series of reactions and fixation of the reaction conditions to estimate them. Rather, it is done by estimating the property after dissolving it directly in distilled water in the presence of another drug with it in a mixture. It is considered one of the successful methods in the assessment, especially for properties that are close in spectrum absorption for which it is not possible to find ways to separate the mixture more accurately than this proposed method without overlapping and the effects of one on the other.  The proposed method in this research was successful in the estimation of both drugs ciprofloxacin and cefalexin in a mixture without drug interaction with the other.